The Fragmentation of Sápmi: A Nordic Model of Settler Colonialism - McGuire, Lynette (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
While the Nordic countries are frequently renowned as some of the most peaceful societies in the world, such a conception of peace cannot fully encapsulate the experiences of the Sámi. Likewise, the global movement toward settler-Indigenous reconciliation since the 1960s has set the Nordic response apart from the rest of the world. Building upon existing understandings of internal colonialism and structural violence, this paper analyzes how pragmatic attempts by Finland, Norway, and Sweden to reconcile with the Sápmi have constituted a unified Nordic model of continued settler colonialism, as well as how differences between the National Sámi parliaments contribute to that model. Finally, this paper examines the impact that the Nordic model of settler colonialism has had on pan-Sámi politics, particularly concerning problems of Sámi reunification since the fall of the Soviet Union.